Family Resilience and Chronic Illness : Interdisciplinary and Translational Perspectives - Welch, Ginger L.; Harrist, Amanda W. (Springer International Publishing : Imprint: Springer, 2017)
This interdisciplinary volume offers theoretical, empirical, and practical insights into the strengths of families beset by chronic health issues. Featuring topics that run the lifespan from infancy to late adulthood, its coverage reflects both the diversity of family challenges in long-term illness and the wealth of effective approaches to intervention. The component skills of resilience in life-changing circumstances, from coping and meaning making to balancing care and self-care, are on rich display in a framework for their enhancement in therapy. The book's expert contributors include tools to aid readers in the learning and teaching of concepts as they model respectful, meaningful research methods and ethical, non-judgmental practice. Among the topics covered: Helping families survive and thrive through the premature birth of an infant. Enhancing coping and resiliency among families of individuals with sickle cell disease. A family science approach to pediatric obesity treatment. Risk and resilience of children and families involved with the foster care system. Strengthening families facing breast cancer: emerging trends and clinical recommendations. The unfolding of unique problems in later life families. With its mix of practical and empirical expertise, Family Resilience and Chronic Illness: Interdisciplinary and Translational Perspectives has much to offer both researchers in the family resilience field and mental health practitioners working with clients with chronic illness. .
Keywords: Social sciences.; Public health.; Families.; Families -- Social aspects.; Developmental psychology.; elektronické knihy; electronic books